Kandungan Logam Berat Pb, Cd, Hg, As pada Bunga Telang (Clitoria ternatea L.) dari Kabupaten Sleman, Daerah Istimewa Yogyakarta - Andriani, Disa; Puspitasari, Dian; Pratimasari , Diah (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2023)
Telang flower (Clitoria ternatea L.) is a plant that has many health benefits. Butterfly pea flowers have been proven to be used as a food coloring agent. Research on the benefits of telang flower as a colorant for ice lolly, where products using dyes from telang flowers have a color intensity comparable to products using synthetic food grade dye blue diamond Cl 42090 with a color that remains stable when frozen in the freezer. In addition, the telang flower can also be used as a natural antioxidant. Telang flowers can also be used as an effective sunscreen cream. Telang flower has many health benefits, so when using it, you must meet the safety standards set by the government. This research was conducted to look at the metal contamination found in the ethanol extract of the Telang flower. Preparation of the extract by maceration method with 70% ethanol solvent for 3 days. Heavy Metal Test (Lead, Cadmium, Arsenic and Mercury) was performed using Atomic Absorption Spectroscopy (AAS). The test results showed that the telang ?flower extract was still below the maximum limit allowed by the government, namely for lead d 10 mg/kg, cadmium d 0.3 mg/kg, arsenic d 5 mg/kg, mercury d 0.5 mg/kg. This shows that the ethanol extract of telang flower is safe to use.